Association between Personal Hygiene Behavior and Sleeping Quality on Scabies Incidence - Hidayat, Nur; Putri Nurlela, Intan; Nurapandi, Adi; Utami Asmarani, Sri; Setiawan, Henri (Alta Dharma Publisher, 2022)
Introduction: Scabies is a skin disease still often found in Indonesia and remains a public health problem. According to the World Health Organization (WHO), the incidence of Scabies in 2014 was 130 million people in the world. Objective: This study aims to determine the correlation between personal hygiene behavior in bathing and sleeping with the incidence of Scabies in students at Manhajul Ulum Islamic Boarding School. Method: Descriptive quantitative research using correlation and retrospective research design was used in this research. The total population is 90 students who suffer from Scabies and who do not suffer from Scabies at the Manhajul Ulum Islamic Boarding School. The total sampling technique was used to select the respondents. Results: Statistical test results obtained that there is a relationship between personal hygiene behavior and bathing behavior with the incidence of Scabies (p = 0.023 <0.05), and there is a relationship between personal hygiene behavior and sleeping behavior with the incidence of Scabies (p = 0.011 <0.05). Conclusion: The conclusion of this study states that there is a significant relationship between personal hygiene behavior, bathing behavior, and sleeping behavior with the incidence of Scabies in students at the Manhajul Ulum Islamic Boarding School. Recommendation: This study recommends that Islamic boarding school managers and students improve personal hygiene regarding bathing and sleeping behavior